Vloga slovenskih krovnih organizacij SKGZ in SSO pri politični participaciji Slovencev v Italiji - Brezigar, Sara (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2020)
The paper discusses the role of the Slovene umbrella organizations SKGZ and SSO in the field of political participation of Slovenes in Italy. From a theoretical point of vhew the authors highlight important aspects of the role of umbrella organizations as a view of political participation of national minorities. Moreover, based on the results of an empirical study on representation in organizations of the Slovene community in Italy, they analyse major dilemmas of their functioning related to representation, decision-making processes (in the organization) and leadership and introduce a discussion on possible solutions.
Keywords: Italija; krovne organizacije; politična participacija; SKGZ; slovenska manjšina; SSO